The Impact of Overcrowding on Prisoners' Rights - Brivik, Adva (Institute of Criminology, 2014)
This dissertation will focus on the effect of overcrowding of inmates in prisons, showing that due to Government policies, a self defeating cycle is in place whereby instead of leading to the reintegration of prisoners, the prison system is actually creating more problems for the society that it is trying to protect. The situation has not suddenly appeared overnight and a brief discussion as to the complicated history of South Africa's penal system, specifically up until the end of white minority rule in 1994, is necessary. Further, this dissertation intends to look at South African law as well as well as international treaties. Following on from this a case by case look at inmates' rights, this relates to both those that have been sentenced and those awaiting trial, and ensuring that they are invoked. Despite legislative support for the protection of inmates' rights the situation at present is clearly unacceptable and as such, various reasons for this will be explored, including the problems surrounding minimum sentence legislation, the ability of correctional services to deal with court challenges and overcrowding and HIV/ AIDS. Lastly, after a discussion of South African and international case law on the matter, with a review of the viability of the various alternatives to imprisonment. Finally, the common misconceptions that are often based on feelings of victimisation, whereby 'people are sent to prison as punishment and not for punishment' will be clarified.